Morphological Study of the Kidney in Relation to Age (Bangladesh Journal of Anatomy, 2009)
Objective: The study was done to standardize the morphological data of kidney in relation to the age of person. Materials and methods: The study was done on kidneys collected from 50 postmortem cases, age from 11 years to 80 years, during the period of July 2005 to December 2005 in the department of Anatomy, M.A.G. Osmani Medical College, Sylhet. Kidneys were collected with legal permissions from the authority in charge of the morgue of Forensic Medicine department of M.A.G. Osmani Medical College, Sylhet. Among the cases 32 were male and 18 female. The kidneys were fixed in 10% formosaline. The weight, length, breadth and thickness were recorded. Result: Data were collected in 3 groups, lower age (11- 25 years), middle age (26-40 years) and higher age (41-80 years) groups. The mean weights of the kidney in 3 groups were found as 88.53 gm, 95.25 gm and 91.62 gm respectively. Similarly the mean lengths were recorded as 8.12 cm, 9.12 cm and 8.73 cm. the mean breadth were 4.46 cm, 4.31 cm and 3.58 cm. the mean thickness in these three groups were 1.72 cm, 2.19 cm and 1.48 cm respectively. Conclusion: It can be concluded that the gross values of different dimensions of the kidney, except the breadth, increases up to the age of 40 years. With further advance of age they are gradually decreased. The breadth was found greater in lower age group. Key words: Morphology of kidney, age   doi: 10.3329/bja.v7i1.3012 Bangladesh Journal of Anatomy January 2009, Vol. 7 No. 1 pp. 19-21